Ultra-trace Measurements in the WAIS Divide 06A Ice Core - Aydin, Murat; Saltzman, Eric (IEDA: US Antarctic Program Data Center, 2015)
These data contain the results of gas chromatography mass spectrometry (GC-MS) analysis of 207 samples from the WAIS Divide 06A ice core. The trace gases found in the 207 samples are ethane (C2H6), propane (C3H8), n-butane (n-C4H10), carbonyl sulfide (COS), carbon disulfide (CS2), methyl chloride (CH3Cl), and methyl bromide (CH3Br).